Odpowiedzi

2010-01-29T10:45:42+01:00
5(3b+2)
4(4b-3c)
12(x+3y)
y(1-3)
3(5a²+4b²)
8(3x²-2y)
4(3a²-2b)
5(2n-3m)
2010-01-29T10:48:48+01:00
15b+10= 5(3b+2)
16b-12c= 4(4b-3c)

12x+36y= 12(x+3y)
y-3y= y(1-3) =-2y
15a²+12b²= 3(5a²+4b²)


24x²-16y= 8(3x²-2y)
12a²-8b=4(3a²-2b)
10n-15m=5(2n-3m)
2010-01-29T11:01:49+01:00
B)15b+10= 5(3b+2)
16b-12c= 4(4b-3c)
c)12x+36y= 12(x+3y)
y-3y= y(1-3)
15a²+12b²= 3(5a²+4b²)
d)24x²-16y= 8(3x²-2y)
12a²-8b= 4(3a²-2b)
10n-15m= 5(2n-3m)

Mam nadzieje, że pomogłam
Pozdrawiam!!